Global reprogramming of transcription and metabolism in Medicago truncatula during progressive drought and after rewatering - Zhang, Ji-Yi (Plant Cell Environ, 2014)
Medicago truncatula is a model legume forage crop native to the arid and semi-arid environments of the Mediterranean. Given its drought-adapted nature, it is an ideal candidate to study the molecular and biochemical mechanisms conferring drought resistance in plants. Medicago plants were subjected to a progressive drought stress over 14 d of water withholding followed by rewatering under controlled environmental conditions. Based on physiological measurements of plant water status and changes in morphology, plants experienced mild, moderate and severe water stress before rehydration. Transcriptome analysis of roots and shoots from control, mildly, moderately and severely stressed, and rewatered plants, identified many thousands of genes that were altered in expression in response to drought. Many genes with expression tightly coupled to the plant water potential (i.e. drought intensity) were identified suggesting an involvement in Medicago drought adaptation responses. Metabolite profiling of drought-stressed plants revealed the presence of 135 polar and 165 non-polar compounds in roots and shoots. Combining Medicago metabolomic data with transcriptomic data yielded insight into the regulation of metabolic pathways operating under drought stress. Among the metabolites detected in drought-stressed Medicago plants, myo-inositol and proline had striking regulatory profiles indicating involvement in Medicago drought tolerance. Global transcriptional and metabolic responses to drought and rewatering were investigated in Medicago truncatula, a naturally drought-adapted model legume species. Integration of metabolomic and transcriptomic data yielded insights into the regulation of metabolic pathways underlying drought-stress adaptation. Many genes and metabolites with expression tightly coupled to drought intensity were identified, suggesting active involvement in Medicago drought resistance. These could prove useful targets for future translational approaches to improve closely related crop plants such as common bean, soybean and pea.